Cross-Border Collaboration in Disaster Management - Klein, Miriam Isabelle (Produktion und Energie, 2022)
In recent years, disaster events spreading across national borders have increased, which requires improved collaboration between countries. By means of an agent-based simulation and an empirical study, this thesis provides valuable insights for decision-makers in order to overcome barriers in cross-border cooperation and thus, enhance borderland resilience for future events. Finally, implications for today's world in terms of globalization versus emerging nationalism are discussed.